2018
DOI: 10.3390/rs10101514
|View full text |Cite
|
Sign up to set email alerts
|

Radar Path Delay Effects in Volcanic Gas Plumes: The Case of Láscar Volcano, Northern Chile

Abstract: Modern volcano monitoring commonly involves Interferometric Synthetic Aperture Radar (InSAR) measurements to identify ground motions caused by volcanic activity. However, InSAR is largely affected by changes in atmospheric refractivity, in particular by changes which can be attributed to the distribution of water (H 2 O) vapor in the atmospheric column. Gas emissions from continuously degassing volcanoes contain abundant water vapor and thus produce variations in the atmospheric water vapor content above and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 102 publications
0
18
0
Order By: Relevance
“…Wooster (2001) described the rapid cooling behavior of the Lascar dome as precursor activity following the 1993 eruption, while a recent study of the 2013 explosion utilized seismic wave interferometry to depict variations in the seismic velocity and consequently speculated about the preeruptive deformation of a magmatic/hydrothermal reservoir (González et al, 2016). A shallow hydrothermal system as depicted by magnetotelluric and seismic data (Díaz et al, 2012;Hellweg, 2000) influences the degassing activity of Lascar (Bredemeyer et al, 2018;Tassi et al, 2009). These degassing processes have been suggested to be the source of the tremors observed during the 1994-1995 period of unrest (Hellweg, 2000), and they are probably associated with the increase in long-period (LP) events preceding an eruption (González et al, 2016).…”
Section: Study Area and Explosive History Of Lascar Volcanomentioning
confidence: 99%
“…Wooster (2001) described the rapid cooling behavior of the Lascar dome as precursor activity following the 1993 eruption, while a recent study of the 2013 explosion utilized seismic wave interferometry to depict variations in the seismic velocity and consequently speculated about the preeruptive deformation of a magmatic/hydrothermal reservoir (González et al, 2016). A shallow hydrothermal system as depicted by magnetotelluric and seismic data (Díaz et al, 2012;Hellweg, 2000) influences the degassing activity of Lascar (Bredemeyer et al, 2018;Tassi et al, 2009). These degassing processes have been suggested to be the source of the tremors observed during the 1994-1995 period of unrest (Hellweg, 2000), and they are probably associated with the increase in long-period (LP) events preceding an eruption (González et al, 2016).…”
Section: Study Area and Explosive History Of Lascar Volcanomentioning
confidence: 99%
“…Matthews et al (1997) proposed a continuous deepening of the crater floor associated with a high rate of degassing from fumaroles within the active crater; this degassing phenomenon was subsequently identified by an InSAR investigation (Pavez et al, 2006) and further confirmed by continuous monitoring using the high-resolution German satellite TerraSAR-X (Richter et al, 2018), which also showed that the deformation rate appeared to be largely unaffected by the most recent explosive eruptions in 2013 and 2015. A shallow hydrothermal system depicted by magnetotelluric and seismic data (Díaz et al, 2012;Hellweg, 2000) seems to influence the active degassing at Lascar (Bredemeyer et al, 2018;Tassi et al, 2009). These degassing processes have been suggested to be the source of the tremors observed during the 1994-1995 period of unrest (Hellweg, 2000), and they are probably associated with the increase in longperiod (LP) events preceding an eruption (González et al, 2016).…”
Section: Study Area and Explosive History Of Lascar Volcanomentioning
confidence: 99%
“…This also favours the mechanism of degassing transporting more energy through hot fumarolic gases as a result of a higher magmatic gas flux into the atmosphere. The entire gas pulse accompanying the eruption expelled at least 170 metric tons of SO2 in only 100 minutes, which is approximately half the amount of SO2 that Lascar volcano usually emits throughout a whole day in a non-eruptive period (Tamburello et al, 2014;Bredemeyer et al, 2018). Using the molar ratios of Tamburello et al 2014, we additionally obtain equivalents of at least 5,440 metric tons of H2O and 230 metric tons of CO2 that were released during these 100 minutes.…”
Section: Water Infiltration Into a Cooling Lava Dome At Lascarmentioning
confidence: 99%
See 2 more Smart Citations